A Systematic Literature Review on Resilient Digital Transformation, Examining How Organizations Sustain Digital Capabilities - Thira Chavarnakul; Li Da Xu; Zhuming Bi; Achyut Shankar; Gaurav Dhiman; Wattana Viriyasitavat; Danupol Hoonsopon (HighTech and Innovation Journal)
In an era marked by relentless technological shifts and market volatility, digital transformation (DT) alone is insufficient. Organizations must develop Resilient Digital Transformation (RDT)—the organizational capabilities required to sustain DT over a medium-term horizon—to navigate these challenges effectively. This study primarily aims to propose a guideline for fostering RDT. Drawing on the PRISMA guidelines and a systematic review of 77 peer-reviewed papers, this study identifies and synthesizes key targets and drivers across three core pillars: Technology, Organization, and External Environment. These elements collectively foster organizational resilience. Specifically, this study highlights how adaptability, innovation, and scalability form the technological underpinnings of sustained digital maturity; meanwhile, effective governance frameworks, ongoing workforce development, and supportive cultures promote organizational agility. Externally, proactive stakeholder engagement, responsiveness to market shifts, and robust regulatory compliance help ensure the long-term viability of digital initiatives. The findings contribute to the existing literature by unifying an integrative framework illustrating how organizations can sense, seize, and reconfigure resources to embed resilience across strategic and operational processes. By moving beyond static maturity models, the framework stresses the continuous nature of digital transformation, offering both academics and practitioners a structured approach to sustaining competitive advantage amid incessant disruptions.